CHARACTERIZATION OF THE PEANUT PRODUCTION SYSTEMS IN THEIR MAIN AGROECOLOGICAL REGIONS IN BENIN - Didagbe, Oscar Yedeou; Houngnandan, Pascal; Dedehouanou, Houinsou; Sina, Haziz; Bello, Daouda Orou; Toukourou, Fatiou; Baba- Moussa, Lamine (European Scientific Journal, ESJ, 2015)
The aim of the present study was to characterize the peanut production systems in two agro-ecological zones (AEZ) in order to pave the ways for the improvement of existing Agriculture-Farming Integrated Productivity Systems of Benin. Thus, 203 peanut producers were investigated in four rural communes in the AEZ III and AEZ V of Benin. The data collected relate to socioeconomic characteristics of producers, farming management practices, utilization of the peanuts’ fans, market prices of peanut, input quantities and market prices, revenues for the crop production year 2013-2014, constraints on peanut production and farming methods. The results indicate that male producers are mostly producing peanut (69.7 %). The producers of the Center of Benin are significantly more experienced (17.76±0.72) than those of the North (14.33±0.77). Our observations show that two varieties are grown of which one is improved (Carder: 2087.68 ± 154.06 kg/ha) and another is local (Moto: 1309.38 ± 119.25 kg/ha). No significant difference (P > 0.05) exists between the two areas of production in relation to the yields recorded for the peanuts production in the year 2013- 2014. The major production constraints listed by the majority of producers (85 %) are the poor quality of seed, the lack of specific inputs and labor, the climatic hazards, mainly the pockets of drought, the poor distribution of rainfall and the excessive temperatures. In the two surveyed production areas, the majority of peanut producers (60 %) do not feed animals neither with dead leaves nor with food supplementation or fodder.